2020
DOI: 10.5815/ijeme.2020.02.03
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study between Cloud Energy Consumption Measuring Simulators

Abstract: Cloud computing is the study of using remote servers which are hosted on the internet to deliver on-demand computing resources on pay-for-use basis rather than a local server. Due to high energy consumption in cloud computing environments, it has become the main area of research. The amount of energy consumption becomes difficult to determine in real cloud computing infrastructure. In recent years some simulation tools have been developed to analyze the energy consumption in cloud computing environments for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…These encouragements from society can strengthen the confidence of leukemia children in treatment and help them establish a positive treatment attitude. In addition, we make the volunteer service team cooperate with other caring organizations, build a public welfare platform and carry out promotional activities, appealing to the society to care for leukemia children, and using the power of social media to make leukemia children and families feel the warmth of society [18].…”
Section: Explore and Establish "Real" Service Modelmentioning
confidence: 99%
“…These encouragements from society can strengthen the confidence of leukemia children in treatment and help them establish a positive treatment attitude. In addition, we make the volunteer service team cooperate with other caring organizations, build a public welfare platform and carry out promotional activities, appealing to the society to care for leukemia children, and using the power of social media to make leukemia children and families feel the warmth of society [18].…”
Section: Explore and Establish "Real" Service Modelmentioning
confidence: 99%
“…This paper examines current technologies designed to increase energy savings for largescale CC infrastructures while not sacrificing the QoS and efficiency by analyzing all possible locations of cloud infrastructure that are responsible for significant energy usage. Muhammad Hassaan [15] suggested that it has become the main field of research due to the increased energy usage of CC environments. In real CC networks, the amount of energy usage becomes hard to estimate.…”
Section: Features Comparison Of CC and Mccmentioning
confidence: 99%
“…When it comes to designing energy models, there are a few things to bear in mind. Muhammad Hassaan [15] suggested that the simulation framework for CloudSim is a Java-based simulation toolkit that can design extremely large-scale clouds and support communication among cloud system components. It's an event-based simulator.…”
Section: A Common Cloud Simulatorsmentioning
confidence: 99%
“…Asphalt and asphalt mixture testing is a professional basic course for students majoring in transportation engineering, mainly studying the composition, performance testing, and application of asphalt pavement materials [3,4]. By mastering the technical characteristics, indicators, and evaluation methods of asphalt pavement materials, practical engineering problems can be solved, while also laying the foundation for the subsequent study of relevant professional courses.…”
Section: Introductionmentioning
confidence: 99%